Place‐based management can reduce human impacts on coral reefs in a changing climate. Issue 4 (25th April 2019) - Delevaux, Jade M. S.; Stamoulis, Kostantinos A.; Whittier, Robert; Jupiter, Stacy D.; Bremer, Leah L.; Friedlander, Alan; Kurashima, Natalie; Giddens, Jonatha; Winter, Kawika B.; Blaich‐Vaughan, Mehana; Burnett, Kimberly M.; Geslani, Cheryl; et al.
Abstract: Declining natural resources have contributed to a cultural renaissance across the Pacific that seeks to revive customary ridge‐to‐reef management approaches to protect freshwater and restore abundant coral reef fisheries. We applied a linked land–sea modeling framework based on remote sensing and empirical data, which couples groundwater nutrient export and coral reef models at fine spatial resolution. This spatially explicit (60 × 60 m) framework simultaneously tracks changes in multiple benthic and fish indicators as a function of community‐led marine closures, land‐use and climate change scenarios. We applied this framework in Hā'ena and Ka'ūpūlehu, located at opposite ends of the Hawaiian Archipelago to investigate the effects of coastal development and marine closures on coral reefs in the face of climate change. Our results indicated that projected coastal development and bleaching can result in a significant decrease in benthic habitat quality and community‐led marine closures can result in a significant increase in fish biomass. In general, Ka'ūpūlehu is more vulnerable to land‐based nutrients and coral bleaching than Hā'ena due to high coral cover and limited dilution and mixing from low rainfall and wave power, except for the shallow and wave‐sheltered back‐reef areas of Hā'ena, which support high coral cover and act as nursery habitat for fishes. By coupling spatially explicit land–sea models with scenario planning, we identified priority areas on land where upgrading cesspools can reduce human impacts on coral reefs in the face of projected climate change impacts.